2003
DOI: 10.1038/ni895
|View full text |Cite
|
Sign up to set email alerts
|

TCR ligand discrimination is enforced by competing ERK positive and SHP-1 negative feedback pathways

Abstract: Functional discrimination between structurally similar self and foreign antigens is a main attribute of adaptive immunity. Here we describe two feedback mechanisms in T lymphocytes that together sharpen and amplify initial signaling differences related to the quality of T cell receptor (TCR) engagement. Weakly binding ligands predominantly trigger a negative feedback loop leading to rapid recruitment of the tyrosine phosphatase SHP-1, followed by receptor desensitization through inactivation of Lck kinase. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
453
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(494 citation statements)
references
References 61 publications
38
453
1
2
Order By: Relevance
“…Whether the previously reported loss of lipid domain association of CD4 in Th2 cells might thus represent a secondary effect of this quantitative change and the alteration in signaling leads to this, will require additional investigation. Our description of very early acting SHP-1-dependent negative feedback in controlling the TCR signal quality and duration [19], along with the evidence from this and other laboratories that the early phosphorylation of TCR-associated components precedes synapse formation [22], is consistent with the view that these previously reported aspects of CD4 behavior may be a downstream consequence rather than a primary cause of the Th2 pattern of signaling.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Whether the previously reported loss of lipid domain association of CD4 in Th2 cells might thus represent a secondary effect of this quantitative change and the alteration in signaling leads to this, will require additional investigation. Our description of very early acting SHP-1-dependent negative feedback in controlling the TCR signal quality and duration [19], along with the evidence from this and other laboratories that the early phosphorylation of TCR-associated components precedes synapse formation [22], is consistent with the view that these previously reported aspects of CD4 behavior may be a downstream consequence rather than a primary cause of the Th2 pattern of signaling.…”
Section: Discussionsupporting
confidence: 90%
“…Control 5C.C7 Th1 cells showed substantial levels of the p23 phosphorylated form of TCR f chain, whereas those exposed to antigen in the presence of anti-CD4 showed little p23 TCR f generation and predominant p21 production, consistent with our earlier study. Our previous studies have shown that in addition to CD4-associated Lck, there is a separate pool of Lck associated with the TCR [19], providing a source of kinase for generation of the antigen-induced p21f seen in this experiment even when CD4-Lck is not involved. …”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Multiple mechanisms have been postulated to generate these differences in Erk dynamics. Recently, a positive feedback loop in which Erk phosphorylates Lck in a regulatory manner to prevent SHP-1 deactivation of Lck was shown to sustain TCR signaling (7). A mathematical modeling effort has demonstrated how the balance between this novel Erk positive feedback and negative feedback via phosphatase-mediated deactivation of molecules proximal to the TCR allows for sensitivity in ligand discrimination (8).…”
Section: Introductionmentioning
confidence: 99%